Methods and strategies of process research : integrative approaches in translation studies - Dimitrova, Birgitta Englund (John Benjamins, 2015)
The volume includes contributions on the cognitive processes underlying translation and interpreting, which represent innovative research with a methodological and empirical orientation. The methodological section offers an assessment/validation of different time lag measures; discusses the challenges of interpreting keystroke and eye-tracking data in translation, and triangulating disfluency analysis and eye-tracking data in sight translation research. The remainder of the volume features empirical studies on such topics as: metaphor comprehension; audience perception in subtitling research.